Effectiveness of monthly and fortnightly anti-VEGF treatments for age-related macular degeneration - Nunes,Renata Portella (2019)
ABSTRACT Purpose: To study the efficacy and safety of treatments with ranibizumab and bevacizumab for exudative age-related macular degeneration. Methods: A parallel randomized clinical trial was conducted to compare the efficacy and safety of three regimens (bevacizumab every month, bevacizumab every 2 weeks, and ranibizumab every month), followed by as-needed retreatments, for 1 year, in previously untreated individuals with age-related macular degeneration. The primary outcome was change in visual acuity and in central macular thickness after 1 year of follow-up. Subjects were assigned randomly to one of the three groups in a 1:1:1 ratio, and investigators and examiners were blinded to the randomization results. Results: We included 15 patients in each group. After 1 year of follow-up, we found statistically significant improvements in visual acuity and central macular thickness reduction in all groups. However, we found no statistically significant differences between the three groups. Conclusions: The bi-weekly follow-up was effective and we found no significant differences in efficacy or safety between the treatments with ranibizumab and bevacizumab.